This preview shows page 1. Sign up to view the full content.
Unformatted text preview: t = 0 we have x 1 (0) = C 1 e + C 2 e 2(0) = C 1 + C 2 . Similarly, x 2 ( t ) = 2 C 1 e tC 2 e 2 t , gives x 2 (0) = 2 C 1 e ( 0)C 2 e 2(0) = 2 C 1C 2 . Together with x 1 (0) = 2 , x 2 (0) = 3 we have the following system of equations, C 1 + C 2 = 1 2 C 1C 2 = 3 Rewrite the equation in matrix form 1 1 21 C 1 C 2 = 1 3 , and using Mathcad we nd the solution is C 1 C 2 = 4 31 3...
View
Full
Document
This note was uploaded on 10/04/2011 for the course MAP 4231 taught by Professor Dr.han during the Spring '11 term at UNF.
 Spring '11
 Dr.Han

Click to edit the document details